Survey of public attitudes towards imminent death donation in the United States. Issue 1 (4th August 2020) - Washburn, Laura; Galván, Nhu Thao Nguyen; Moolchandani, Priyanka; Price, Matthew B.; Rath, Smruti; Ackah, Ruth; Myers, Kevin A.; Wood, R. P.; Parsons, Sandra; Brown, Ryan P.; Ranova, Elitza; Goss, Matthew; et al.
Abstract : Imminent death donation (IDD) is described as living organ donation prior to a planned withdrawal of life‐sustaining care in an imminently dying patient. Although IDD was ethically justified by United Network for Organ Sharing, the concept remains controversial due to presumed lack of public support. The aim of this study was to evaluate the public's attitudes towards IDD. A cross‐sectional survey was conducted of US adults age >18 years (n = 2644). The survey included a case scenario of a patient with a devastating brain injury. Responses were assessed on a 5‐point Likert scale. Results showed that 68% ‐ 74% of participants agreed or strongly agreed with IDD when posed as a general question and in relation to the case scenario. Participants were concerned about "recovery after a devastating brain injury" (34%), and that "doctors would not try as hard to save a patient's life" (33%). Only 9% of participants would be less likely to trust the organ donation process. In conclusion, our study demonstrates strong public support for IDD in the case of a patient with a devastating brain injury. Notably, participants were not largely concerned with losing trust in the organ donation process. These results justify policy change towards imminent death donation. Abstract : A large‐scale national survey assesses public attitudes toward imminent death donation and identifies concerns of losing trust in the organ donation process.